Civil and Political Rights With The Case Study Myanmar Military Coup - Habib Khatami Panjaitan (Syntax Literate, 2022)
Civil and political rights are rights which inherent to all of people around the world, it cannot be taken by anyone including a state. These rights are protected on international agreement such as The Universal Declaration of Human Right in 1948, and International Covenant on Civil and Political Right 1966. The aims of this paper are to analyse civil and political right phenomenon in the world. Myanmar Military Coup started on February with the argument that President Election of Myanmar was not legitimate on other hand, Myanmar Society assumed that President Election of Myanmar was legitimate by the constitution. Along with it, the writer found that there was human right violence that violated during the Myanmar Military Coup. To aggrandize this paper, the writer is going to use concept of human right which explained about all of right that inherent which had by all of people, and international convention concept which clearly explained about right that be protected and can be violated. This research uses qualitative method which based on secondary data that collect from books, journals, article, news, and validity website that can help this paper